Score for Neonatal Acute Physiology Perinatal Extension II (SNAPPE II) as the predictor of neonatal mortality hospitalized in neonatal intensive care unit - James Thimoty; Dany Hilmanto; Tetty Yuniati (Indonesian Pediatric Society, 2009)
Background The assesment of severity of illness with scoringsystem has been used to predict neonatal mortality in neonatalintensive care unit (NICU). Score for Neonatal Acute PhysiologyPerinatal Extension II (SNAPPE II) is the best scoring systemalthough most of the studies were commonly conducted indeveloped countries.Objective To evaluate SNAPPE II as the predictor of neonatalmortality in NICU Hasan Sadikin General Hospital (HSGH)Ban dung.Methods This was a longitudinal observational study. All neonateshospitalized in NICU HSGH during the period of August toNovember 2008 were investigated according to SNAPPE IIrequirements. We excluded subjects admitted more than 48hours of age, who were discharged or moved to intermediatenewborn care ward less than 24 hours after admission. Predictionof mortality and determination of SNAPPE II cut-off point wereanalyzed using logistic regression. Discrimination was analyzedusing receiver operating characteristic (ROC) and calibration wasanalyzed using Hosmer-Lemeshow goodness-of-fit.Results Forty subjects fulfilled the inclusion criteria. There was agood relation between SNAPPE II and mortality prediction (P =0.007). The cut-off point for predicting mortality was 51. SNAPPEII showed good discrimination with AUC 0.933 (95% CI 0.843to 1.0) and good calibration 1.69 (P = 0.97).Conclusion SNAPPE II can be used to predict neonatal mortalityin NICU similar to that found in developed countries.